ANALISIS TANTANGAN BELAJAR SISWA SD YANG MENGALAMI BROKEN HOME DI SDN 08 BIAU - Rosita Sinyor; Muh. Khaerul Ummah BK; Mustakim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Disharmonious family conditions are often a factor hindering students' learning success at school. This study aims to analyze the learning challenges experienced by elementary school students from broken homes and the mentoring strategies implemented by homeroom teachers and principals. The study used a qualitative approach with a case study method at SDN 08 Biau, Buol Regency, with a student from a broken home, the homeroom teacher, and the principal as subjects. Data were collected through interviews, observations, and documentation, then analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results show that students from broken homes face challenges such as decreased learning motivation, difficulty concentrating, emotional instability, and vulnerability to peer teasing. Lack of parental support and unfavorable home conditions also impact students' academic development. The strategies implemented include individual guidance, adjusted evaluations, motivation, study groups, and supporting activities such as watching educational films together. This mentoring has been proven to help increase students' enthusiasm for learning, participation, and self-confidence. This research is expected to serve as a reference for teachers and schools in designing learning strategies that are friendly to students from broken homes.